Faktor Yang Mempengaruhi Perilaku Mengemudi Tidak Aman Pada Sopir Bus Trayek Jember Kencong Lumajang - Ahmad Alfani Rohman Noviandi; Ragil Ismi Hartanti; Prehatin Trirahayu Ningrum (Politeknik Negeri Jember, 2017)
The number of bus traffic accidents has increased each year. One of the causes of the accident is the driver behavior. Human behavior determined by three factors are predisposing factors, enabling factors and reinforcing factor. Purpose of this research was to analyze related the risk factors with unsafe driving bahaviour driver bus in Jember-Kencong-Lumajang route. This research use analytic observation research method with cross sectional approach. Data retrieval method used observation, interview and documentation study.Sampling method used simple random sampling with a sample number of 37 people. From the results of research that variables like working hours (p = 0.106), working period (p = 0.511), breaking duration (p = 0.944), working time (0.581), vehicle condition (p = 0.909), weather conditions (p = 0.628), income (0.973) and family support variables (p = 0.495) was not related to unsafe driving behavior. Variable estimated time for one departure (p = 0,021) and level of knowledge (p = 0.027) related to unsafe driving. The conclusions of this research risk factors are estimated time for one departure and level of knowledge related to unsafe driving behavior.